Smoking outside: The effect of the Irish workplace smoking ban on smoking prevalence among the employed - Michael Savage (The Economic and Social Research Institute (ESRI), 2013)
In March 2004, Ireland became the first country to introduce a nationwide workplace smoking ban. The smoking ban increased the non-monetary cost of smoking by prohibiting smoking in the majority of indoor workplaces. The aim of this paper is to examine whether the extra non-monetary cost of smoking was concentrated on the employed. Using two waves of the nationally representative Slán survey, a difference-in-differences approach is used to measure changes in smoking behaviour among the employed relative to the non-working population following the introduction of the workplace smoking ban. By isolating those workers most affected by the ban, the research finds that the workplace smoking ban did not induce a greater reduction in smoking prevalence among the employed population compared to the non-working population. In fact, the evidence suggests a significantly larger decrease in smoking prevalence among the non-workers relative to the employed. This pattern is particularly strong for occasional smokers. Changes in the real price of cigarettes and changes in attitudes to risk are discussed as possible causes for the pattern observed.
Keywords: 330; workplace smoking ban; difference-in-differences; Ireland